PENINGKATAN AKTIVITAS BELAJAR PESERTA DIDIK MELALUI MODEL INKUIRI PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM - Stormadi, Jhoni; ., Zainuddin; ., Suryani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The research is implemented optimally, even teachers tend to use conventional approaches such as lectures. Therefore, it should be carried out inquiry learning in science teaching model in class IV SD Negeri 17 Kensuray. The purpose of this study was to describe whether using an inquiry model can improve the learning student.Teknik and data collection tools such as direct observation, and documentation techniques.This study uses a descriptive method of research is a form of Classroom Action Research (CAR). Based on the results of this study concluded that the implementation of the model of inquiry can increase physical activity pembelajara students in science for students of SDN 17 Kensuray with an increase of 15.00% from 59.33% in the first cycle to 74.33% in sikus II . application of the model of inquiry can enhance mental activity of students in science an increase of 22.00% from 59.33% in the first cycle to 77.33% in the cycle. Keywords: Keywords: Improvement, learners' learning activities, models of inquiry, learning IPA. Abstrak: Penelitian ini memaparkan pelaksanaan pembelajaran model Inkuiri dalam pembelajaran IPA dikelas IV SD Negeri 17 Kensuray. Tujuan dari penelitian ini adalah untuk memaparkan apakah dengan menggunakan Model Inkuiri dapat meningkatkan aktivitas pembelajaran peserta didik.Teknik dan alat pengumpulan data berupa obsevasi langsung, , dan teknik dokumentasi, metode penelitian ini adalah metode deskriptif dengan bentuk penelitian adalah Penelitian Tindakan Kelas (PTK), penerapan model inkuiri dapat meningkatkan aktivitas fisik peserta didik pada pembelajara IPA bagi peserta didik SDN No.17 Kensuray dengan peningkatan sebesar 15,00% dari 59,33% di siklus I menjadi 74,33% di sikus II. penerapan model inkuiri dapat meningkatkan aktivitas mental peserta didik pada pembelajara IPA dengan peningkatan sebesar 22,00% dari 59,33% di siklus I menjadi 77,33% di siklus. Kata kunci : Aktivitas, Pembelajaran IPA, Model Pembelajaran Inquiry